L16 Identifying a therapeutic regimen for cholesterol delivery to huntington's disease brain. (13th September 2016) - Paolo, Eleonora Di; Valenza, Marta; Chen, Jane Y; Ruozi, Barbara; Belletti, Daniela; Cepeda, Carlos; Colombo, Laura; Diomede, Luisa; Cagnotto, Alfredo; Salmona, Mario; Levine, Michael S; Tosi, Giovanni; et al.
Abstract : Background: Several studies provide evidence that brain cholesterol biosynthesis is reduced in several rodent models of Huntington's disease 1, 2, 3 and a similar reduction is also measurable in HD patients, even before disease onset. 4, 5 This dysfunction may be detrimental for neuronal cells, especially given that locally synthesised cholesterol is implicated in neurite outgrowth, synapses formation and maintenance, synaptic activity and integrity, and optimal neurotransmitter release. 6 Aims: We tested the hypothesis that exogenous cholesterol supplementation in the brain of HD mice, by applying different delivery strategies, could rescue aspects of neuronal dysfunction. Methods and results: In our first study, the delivery of cholesterol via brain-permeable polymeric nanoparticles (g7-NPs-Chol) rescued synaptic communication, protected from cognitive decline and partially improved global activity in HD mice (Valenza et al., 2015). In a second ongoing study, cognitive functions are significantly improved in HD mice intrastriatally infused with cholesterol, at a continuous rate, via osmotic minipumps, compared to vehicle-treated and untreated HD mice. More recently, we have also adopted a third innovative strategy based on intranasal delivery of cholesterol and the relative preliminary results will be presented. Conclusions: Our results highlight the positive effect of cholesterol supplementation to reverse the cascade of synaptic and neuronal alterations associated with the disease. To establish the therapeutic regimen for cholesterol administration will advance significantly towards the concept of cholesterol as a candidate drug in HD. References: Valenza et al. J Neurosci 2005 Oct 26;25 (43):9, 932–7 Valenza et al. Hum Mol Genet 2007 Sep 15;16 (18):2, 187–98 Valenza et al. J Neurosci 2010 Aug 11;30 (32):10, 844–50 Leoni et al. Brain 2008 Nov;131 (Pt 11):2, 851–9 Leoni et al. Neurobiol Dis 2013 Jul;55 :37–43 Pfrieger et al. Biochim Biophys Acta 2003 Mar 10;1610 (2):271–80